How often are propositions on the effects of regional trade agreements theoretical curiosa and when should they guide policy? - Lisandro Abrego; Raymond Riezman; John Whalley (The University of Western Ontario, Department of Economics, 2002)
This paper uses computational techniques to assess whether or not various propositions that have been advanced as plausible in the literature on regional trade agreements may actually hold. The idea is to make probabilistic statements as to whether propositions of interest might hold, rather than to restrict assumptions so they unambiguously hold. Our aim is to blend theory and numerical simulation and go beyond the ambiguous analytically derived propositions that dominate the theoretical literature so as to assess the likelihood of propositions holding for particular model specifications.
Keywords: F10; F13; F15; 330; Regional Trade Agreement; Customs Union; Tariff equilibrium; Handelsregionalismus; Zollunion; Modellierung; Theorie